Validation of the Urban Management Policy Implementation Model Using Structural Equation Modeling - Manteghi, Abolghasem; Forati, Hassan; Esmaeilnia shirvani, Kambiz (Digital Transformation and Administration Innovation, 2026)
This study was conducted with the aim of validating the urban management policy implementation model. In terms of methodology, the present research is quantitative–descriptive, and in terms of purpose, it is applied research. The statistical population consisted of 500 managers, experts, and employees associated with urban management. Based on Cochran’s formula, a sample size of 125 participants was selected using simple random sampling. The research instrument was a researcher-developed questionnaire, the validity of which was assessed using face validity, while its reliability was examined using Cronbach’s alpha coefficient; the overall alpha values for all variables were found to be higher than 0.70. Data analysis was conducted using structural equation modeling with SmartPLS software. The results indicated that the path coefficients of strategies to outcomes (0.929), causal conditions to the core category (0.390), the core category to strategies (0.391), contextual conditions to the core category (0.118), intervening conditions to the core category (0.494), contextual conditions to strategies (0.385), and intervening conditions to strategies (0.838) were obtained. To evaluate the model, structural equation modeling was applied using SmartPLS software. All significance values were greater than 1.96, and the standardized coefficients were greater than 0.38, indicating that the model was confirmed. Given that the goodness-of-fit index was obtained as 0.965, the fit of the final model was confirmed. The findings indicate full confirmation of the model derived from the grounded theory approach. It can be concluded that the urban management policy implementation model is valid, and the results of this study can be of interest to authorities responsible for the development and growth of this society.